Energy Efficient Homes: Windows and Skylights - Kathleen C. Ruppert; Wendell A. Porter; Hyun-Jeong Lee (EDIS)
FCS-3276, a 6-page fact sheet by Kathleen C. Ruppert, Wendell A. Porter, and Hyun-Jeong Lee, presents key terms and concerns for windows in Florida homes. Includes references. One of an Energy Efficient Homes series. Published by the UF Department of Family Youth and Community Sciences, June 2008.